Peroneal nerve palsy due to subparaneurial ganglion cyst, a rare variant of intraneural ganglion cyst - Kim, Dongbin; Choi, Jin-Gyu; Son, Byung-Chul (Asian Journal of Neurosurgery, 2018)
Intraneural ganglion cysts are rare mucinous cysts originating within the epineurium of peripheral nerves. Although ganglion cysts are the most frequent tumors of the upper and lower extremities, ganglion cysts rarely result in peripheral nerve compression. We report a case of a 30-year-old patient who presented with foot drop due to subparaneurial ganglion cyst, a variant of an intraneural ganglion cyst. Characteristic magnetic resonance imaging findings were essential in the preoperative diagnosis of intraneural ganglion cyst. The common peroneal nerve and its branches were recognized and traced to its bifurcation during the operation. The articular branches were addressed. The mucious content of the ganglion was typically found to be located within the subparaneurial compartment. Incision of the subparaneurial ganglion cyst was performed, and mucinous content was evacuated. At 2 months after the surgery, paralyzed peroneal nerve was recovered completely. Therefore, early diagnosis of intraneural ganglion, precise identification of the pathology, and proper treatment of the articular branch with atraumatic dissection of ganglion cyst are essential in the successful management of this rare lesion.
Keywords: Common peroneal nerve; cyst; ganglion; intraneural ganglion cyst; peroneal neuropathy